Assinalamentos de Meloidogyne enterolobii em Goiabeira e em Plantas Invasoras no Estado de São Paulo, Brasil - Almeida, Eduardo J.; Alves, Gleina C.S.; Santos, Jaime M.; Martins, Antonio B.G. (My University, 2011)
Information regarding to the geographical distribution of Meloidogyne enterolobii in guava orchards situated in the State of São Paulo, Brazil, are included, with indication of the municipalities from where the nematode was recorded and data of average number of nematodes per 10 g roots. In addition, some weed species rated as new hosts of the guava root-knot nematode are listed.
Records of Meloidogyne enterolobii on guava orchards and weeds in the State of São Paulo, Brazil.